Declaring a public health emergency of international concern : between international law and politics - Eccleston-Turner, Mark; Wenham, Clare (Bristol University Press, 2021)
Addressing multiple empirical case studies, including COVID-19, this multidisciplinary book explores the relationship between international law and international relations to interrogate how a Public Health Emergency of International Concern (PHEIC) is declared and its role in how we collectively respond to outbreaks.